Immunohistochemical localization of receptors for vasoactive intestinal peptide and substance P in human trachea - Fischer, Axel; Kummer, Wolfgang; Couraud, Jean Yves; Adler, D.; Branscheid, D.; Heym, Christine (Laboratory investigation, 1992)
Tissue sections of human cervical trachea were processed for immunohistochemical demonstration of receptors for substance P [using an anti-SP anti-idiotypic antiserum directed toward the ligand binding site of the receptor (Couraud J-Y, Escher ED, Regoli D, Imhof V, Rossignol B, Pradelles P. Anti-substance P anti-idiotypic antibodies: Characterization and biological activities. J Biol Chem 1985;260:9461-9; Couraud J-Y, Maillet S, Grassi J, Frobert Y, Pradelles P. Characterization and properties of anti-substance P antiidiotypic antibodies. Methods Enzymol 1989; 178:275-300)] and vasoactive intestinal peptide (VIP; utilizing a monoclonal antibody toward VIP receptors of an adenocarcinoma cell line (Pichon J, Hirn M, Muller J-M, Mangeat P, Marvaldi J. Anticell surface monoclonal antibodies which antagonize the action of VIP in a human adenocarcinoma cell line (HT29). EMBO J 1983;2:1017-22)], respectively. Mucus cells of the submucosal glands (identified by periodic acid Schiff staining) and neuroendocrine cells of the respiratory epithelium (identified by immunoreactivity to protein gene product 9.5) displayed intense VIP receptor-immunoreactivity. Other tissue components known to respond to exogenously administered VIP, e.g., trachealis muscle, lacked VIP receptor-immunoreactivity, indicating that the monoclonal antibody did not label all receptor subtypes. In accordance with the known pharmacological actions of substance P upon the airways, the anti-substance P receptor antibody labeled the trachealis muscle, submucosal glands, and respiratory epithelium, predominantly at the luminal aspect. Since substance P as well as the structurally related tachykinin, neurokinin A, competed with the anti-receptor antibody in binding to the tissue section, it is likely that both NK-1 and NK-2 receptor subtypes were labeled. The present histochemical approach to localize peptide receptors in the trachea allowed precise analysis of distribution unreached by previous studies using autoradiography. Together with pharmacological data, these morphological findings contribute to the understanding of the sequences of events evoked by the neuropeptides, substance P and VIP, in the human trachea.
Gesehen am 11.11.2025